Exposing viruses: RNA patterns sensed by RIG-I-like receptors. - Rehwinkel, J (2010)
INTRODUCTION: Virus infection triggers a multitude of innate immune pathways that limit viral replication, restrict viral spread and coordinate antigen-specific, adaptive immune responses. Type-I interferons (IFNs) play a crucial role in these events. Innate receptors expressed by the host cell recognize virus presence and signal for rapid IFN induction following infection. SCOPE: This review article discusses recent progress in our understanding of how cytoplasmic RIG-I-like receptors detect infection with RNA viruses.